Efficacy of government laws to contain SARS-CoV-2 spread in Mozambique - António Prista (AOSIS, 2023)
Background: The purpose of this research was to assess the relationship between infection by severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) containment measures implemented in Mozambique and the spread of SARS-CoV-2 from March 17, 2020, to September 30, 2021. Materials and Methods: The number of SARS-CoV-2 tests conducted, the positivity rate for SARS-CoV-2, the daily hospitalization due to COVID-19, and the average number of patients hospitalized with COVID-19 each day were all documented in a database, from which the positivity rate and weekly growth rate were calculated. Seven milestones were specified, each corresponding to a critical date in the legal measures linked to confinement and relaxation of measures. To compare SARS-CoV-2 data, three periods were created for each milestone: Period 1 = 15 days before the date of the decree; Period 2 = Date of the decree to the 15th day after; and Period 3 = from the 16th day to the 30th day of the decree date. ANOVA was used to compare the average values for each indicator between the three times for each milestone. Results: A comparison of all indicators in each milestone's three periods reveals no consistent significant impact of the measures, regardless of the tendency to lockdown or provide relief. Conclusion: No relationship was discovered between the legal measures for SARS-CoV-2 pandemic control and the positive rate and growth rates, as well as the number of hospitalized people. Because it was not feasible to determine the degree of efficacy of each specific measure, this conclusion is related to the measures as a whole.